Benefits and Adverse Events in Younger Versus Older Patients Receiving Adjuvant Chemotherapy for Colon Cancer: Findings From the Adjuvant Colon Cancer Endpoints Data Set - Hubbard, Joleen (American Society of Clinical Oncology, 2012)
PURPOSE: Limited data exist regarding the outcomes of adjuvant therapy in younger patients with stage II and III colon cancer. We examined disease-free survival (DFS), overall survival (OS), recurrence-free interval (RFI), and grade 3+ adverse events (AEs) in younger patients in the 33,574 patient Adjuvant Colon Cancer Endpoints Group data set. PATIENTS AND METHODS: Individual patient data from 24 randomized phase III clinical trials were obtained for survival outcomes, which included 10 clinical trials for AE outcomes. Two age-based cutoff points were used to define younger patients: age younger than 40 years and younger than 50 years. Adjuvant therapy benefit analyses were limited to the nine clinical trials in which the investigational chemotherapeutic arm demonstrated benefit. RESULTS: One thousand seven hundred fifty-eight patients (5.2%) were younger than 40 years, 5,817 patients (17.3%) were younger than 50 years, and only 299 patients (0.9%) were younger than 30 years. No meaningful differences in sex or stage were noted in younger versus older patients. Younger and older patients did not differ in RFI (age, < 40 years: hazard ratio [HR], 1.0; P = .62 and age < 50 years: HR, 1.02; P = .35). Younger patients (both cutoff points), had longer OS and DFS than older patients. In trials demonstrating adjuvant therapy benefit, similar DFS benefit was observed by age. Younger patients experienced less leukopenia and stomatitis, but more frequent nausea/vomiting. CONCLUSION: Among patients on clinical trials, younger and older patients with stage II and III colon cancer had similar RFI and adjuvant therapy benefit. Younger patients have longer OS and DFS, which is likely primarily because of fewer competing causes of death. Adjuvant therapy is beneficial for colon cancer in patients younger than 50 years who meet typical clinical trial eligibility criteria.